If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 4x + -6x = 2x Combine like terms: 4x + -6x = -2x -2x = 2x Solving -2x = 2x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-2x' to each side of the equation. -2x + -2x = 2x + -2x Combine like terms: -2x + -2x = -4x -4x = 2x + -2x Combine like terms: 2x + -2x = 0 -4x = 0 Divide each side by '-4'. x = 0 Simplifying x = 0
| 9(2n-5)=(9n+7)+8 | | 61x^2+56x+4=0 | | -2x+4=4x+16 | | (x-15)(x+3)=0 | | 7(12+y)=4 | | 3t+10=16 | | 3/5n-10=2/5n | | -42=4v-8 | | 5/x-3/5=20 | | 6x+5+7x=34 | | -11b+5+9b=-3b+10 | | 6X+48Y+8Z=2400 | | 20=(150+20p)-(10+30p) | | 61-6x=-11 | | 3y-2=3(2+y) | | (4-3i)(5+i)=0 | | 2n-3(4n+5)=-6+17 | | 2(x-7)=15 | | 4x-2[2-3(3-5x)]=1 | | 4x-2[2-3(3-4x)]=1 | | 2(3x-7)+4=10 | | -7y+3+8y=12-20 | | 2(6x-5)(4x+5)=0 | | -5-5=0 | | 3+log^4(2x+6)=6 | | -16=-2(3+x) | | (-4i)(6i)=0 | | x+2=-2x+14 | | 4(2n-3)=(5n+4)+3 | | [2x+5]=14 | | 20=-36x-4(-6-2) | | 4-(7y-5)=6y-4 |